(untitled) (Research, Society and Development, 2022)
This research aimed to understand the influence of territorialities and their motivations in the use of self-medication in individuals residing in the territory of Itabirinha/Minas Gerais. This is an observational, descriptive, cross-sectional study with a qualitative approach. Intentional type sample, consisting of 13 individuals, of both sexes, aged 40 years or older, users of the Family Health Strategy, the Expanded Center for Family Health and the Social Assistance Reference Center. Qualitative data were obtained through semi-structured interviews based on two themes: 1) Meaning of the medication; 2) Interpretation of the use of the drug in everyday life. For the determination of the data, the technique of Content Analysis, proposed by Bardin, was used. The results of the qualitative data identified the categories for theme 1: (a) Improve the disease and (b) Take away the pain; 2: (a) Good thing and (b) Alleviating pain. These results point to the diversity of meanings and knowledge regarding the medication, as well as the actions of promotion and care in the field of health in the territory studied. It could be concluded that the multi-territorialities experienced by the interviewees are characterized by care actions in the health field based on individual beliefs. Difficulty in accessing medical consultations was identified, which may represent risky situations with self-medication. It is, therefore, a territory marked by political, economic and symbolic instabilities, which have implications for health.